RESEPSI KUM PULAN PUISI MENCINTAIMU PAGI, SIANG, MALAM, KARYA ANDREI AKSANA DARI DIMENSI RESPON ESTETIK WOLFGANG ISER - , Heru Supriyadi; , Prof. Dr. C. Soebakdi Soemanto, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Thesis which is signed with the title Resepsi Kumpulan Puisi Mencintaimu Pagi, Siang, Malam karya Andrei Aksana dari Dimensi Respon Estetik Wolfgang Iser. Has the background of erostism of the loveâs lyric to his sweetheart (wife), interlude agape love and philia love. So in this case, Andrei Aksana describes it in trilogy form time, morning, afternoon and evening. Between sub poetry and another to have good relevantion. Thesis which the writer composes to have theorytical purpose for explaining the problem of variation meaning. It also explains the meaning accordance with the reception, but as the purpose of theory the writer tries to describe the purpose of pragmatism. So in this case, the writer must explain the variation meaning. The poetry anthology also makes synthecism how the reception to give benefite for the reader society. The research concludes that the variation idea in poetry anthology loving you morning, afternoon, evening which is used by the poet, based on the reception of reader effectively. The poetry of Andrei Aksana which the writer observes, I am the lyric, trying to again the great and the deepes love till finding extacism. I am the lyric frequently to feel gloomy, lonely, and also câest la vie So in this case, the writer has synthecism that love, I am the lyric to his sweet heart/(wife) so solid and utopia to gain blunder impression.